Antimicrobial Activity of Excoecaria Agallocha Mangrove Extract in Inhibiting the Growth of Aeromonas Hydrophila by in-Vitro - Dini Siswani Mulia; Berlian Bun’ya Rista; Aman Suyadi; Ikhsan Mujahid; Cahyono Purbomartono (UM Purwokerto Press, 2023)
One of the bacterial diseases that often attack freshwater fish is the red-sore disease, also known as aeromoniasis or Motile Aeromonas Septicemia (MAS). It is caused by bacteria from Aeromonas genus, such as Aeromonas hydrophila. A safe alternative treatment for pathogenic bacteria is the use of antibacterial compounds made from natural ingredients. The Excoecaria agallocha mangrove extract is one of potential alternatives that is useful as natural antimicrobials due to its various contents of antibacterial bioactive compounds. The objective of this study was to determine the antimicrobial activity of E. agallocha mangrove extract in inhibiting the growth of A. hydrophila. The research method was experimental with complete randomized design and factorial pattern of 3 factors (type of plant organ, bacterial strain, and concentration of extract), in 48 treatments and 3 replications. The solvents used consisted of methanol (polar) and n-hexane (non-polar). The plant organs used included leaves and stems. The bacterial strains consisted of GPl-04, GB-01, GL-01, GL-02, GJ-01, and GK-01 with concentrations of leaves and stems extracts of 0, 10, 20, and 30%. The parameter measured was the diameter of inhibition zone, which was done by using disc paper (Kirby Bauer method). Non-parametric Kruskall-Wallis Test and qualitative-descriptive data analysis were applied. The methanol extract of E. agallocha leaves in GJ-01 strain at 10 and 20% concentrations had antimicrobial activity with inhibition zone in 2.55 mm and 2.46 mm, respectively. The n-hexane extract of E. agallocha stem at 20 and 30% concentrations had antimicrobial activity with inhibition zones of 1.88 mm in GPl-04 strain and 1.58 mm in GB-01 strain, respectively. Extract of E. agallocha mangrove exhibited potential as a natural antibacterial to prevent aeromoniasis in fish.